Language development and brain reorganization in a child born without the left hemisphere. (June 2020) - Asaridou, Salomi S.; Demir-Lira, Ö. Ece; Goldin-Meadow, Susan; Levine, Susan C.; Small, Steven L.
Abstract: We present a case of a 14-year-old girl born without the left hemisphere due to prenatal left internal carotid occlusion. We combined longitudinal language and cognitive assessments with functional and structural neuroimaging data to situate the case within age-matched, typically developing children. Despite having had a delay in getting language off the ground during the preschool years, our case performed within the normal range on a variety of standardized language tests, and exceptionally well on phonology and word reading, during the elementary and middle school years. Moreover, her spatial, number, and reasoning skills also fell in the average to above-average range based on assessments during these time periods. Functional MRI data revealed activation in right fronto-temporal areas when listening to short stories, resembling the bilateral activation patterns in age-matched typically developing children. Diffusion MRI data showed significantly larger dorsal white matter association tracts (the direct and anterior segments of the arcuate fasciculus) connecting areas active during language processing in her remaining right hemisphere, compared to either hemisphere in control children. We hypothesize that these changes in functional and structural brain organization are the result of compensatory brain plasticity, manifesting in unusually large right dorsal tracts, and exceptional performance in phonology, speech repetition, and decoding. More specifically, we posit that our case's large white matter connections might have played a compensatory role by providing fast and reliable transfer of information between cortical areas for language in the right hemisphere.